MATEMATIKA DENGAN METODE KOOPERATIF TIPE JIGSAW PADA SISWA KELAS III SD N SENENG WONOSARI GUNUNGKIDUL TAHUN AJARAN 2014/ 2015 - Nindya Ryan Pradewi; Ag. Sri Purnami (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Abstract: The purposes of this research are to describe increasing the activity and achievement of learning mathematics with Cooperative type Jigsaw learning of III grade student of SD Negeri Seneng Wonosari Gunungkidul 2014/2015. Type of this research is classroom action research (CAR). The subject in this researchare  IIIgrade of SD Negeri Seneng Wonosari, consist of 24 students and object this research areactivity and achievement of learning mathematics with Cooperative type Jigsaw learning of III grade student.Technique data collection are observation, tests, and documentation.The percentage of students who reach the KKM on pracycle of 41,6%, on a cycle I was increased to 45,8%, on cycle II increase to 75%. The average value of score for questionnaire sheet is for pracycle the activity of study 2,94 students increase to 3,01 and increase in cycle 2 is3,32. Based on the results of the researsch, it was concluded that the use of metode Cooperative type Jigsaw learning can increase the activity and achievement studied mathematics ofIII grade  student of  SD Negeri Seneng Wonosari.